Genetic diversity and structure of Slovenian native germplasm of plum species (P. domestica L., P. cerasifera Ehrh. and P. spinosa L.) - Ternjak, T.; Barreneche, T.; Šiško, M.; Ivančič, A.; Šušek, A.; Quero-García, J. (Frontiers in Plant Science, 2023)
Slovenia has particular climatic, soil, geographic and historical conditions that lead to long tradition of plum cultivation and use. In this work, a set of 11 SSR and three universal cpDNA markers, as well as flow cytometry, were used to (1) evaluate the genetic diversity of 124 accessions of the three Prunus species (P. domestica L., P. cerasifera Ehrh., and P. spinosa L.), (2) investigate the possible involvement of P. cerasifera and P. spinosa species in P. domestica origin, (3) study the genetic relationships and variability among the most typical P. domestica accessions present in Slovenia. Ten haplotypes of cpDNA were identified and clustered into three groups according to the Neighbor-Joining analysis (NJ). All 11 SSR primer pairs were polymorphic, revealing 116 unique genotypes. A total of 328 alleles were detected with an average value of 29.82 alleles per locus, showing relatively high diversity. Bayesian analysis of genetic structure was used to identify two ancestral populations in the analyses of all three species as well as in a separate set consisting of P. domestica material only. Principal Coordinate Analysis (PCoA) showed that accessions clustered largely in agreement with Bayesian analysis. Neighbor-Joining analysis grouped 71 P. domestica accessions into three clusters with many subgroups that exhibited complex arrangement. Most accessions clustered in agreement with traditional pomological groups, such as common prunes, mirabelle plums and greengages. In this study, the analyses revealed within P. domestica pool valuable local landraces, such as traditional prunes or Bluish plums, which seem to be highly interesting from a genetic point of view. Moreover, complementary approaches allowed us to distinguish between the three species and to gain insights into the origin of plum. The results will be instrumental in understanding the diversity of Slovenian plum germplasm, improving the conservation process, recovering local genotypes and enriching existing collections of plant genetic resources.